An economic analysis of coal desulpharisation by froth flotation to prevent acid rock drainage (ARD) and an economic review of capping covers and ARD treatment processes - Jera, Melody Kudzai (Centre for Bioprocess Engineering Research, 2014)
Includes abstract.